EFL Learners’ Attitudes Toward Native-Like English Pronunciation Versus Intelligibility: A Study of Undergraduate Students - Kholid, M. Ridho; Hidayat, Agus (Newinera Publisher, 2025)
As English becomes increasingly global, particularly in Islamic university contexts, understanding students’ pronunciation goals is crucial for designing effective and culturally responsive instruction. This study explores the attitudes of English Education students at UIN Raden Intan Lampung toward native-like English pronunciation versus intelligibility. This study aims to examine students' beliefs, preferences, and challenges related to English pronunciation, focusing on their aspirations to sound native-like versus their practical need for intelligibility. Using a qualitative descriptive approach, data were collected through semi-structured interviews and reflective journals involving purposively selected participants from various academic years. Thematic analysis was employed to identify recurring patterns and perspectives within the data. The findings reveal ten major themes: students' admiration for native-like pronunciation, prioritization of intelligibility, cultural and religious identity influence, pronunciation anxiety, exposure to diverse English accents, and the lack of explicit pronunciation instruction. While some students aspire to speak like native speakers for prestige or professionalism, most prioritize clear communication over accent imitation. Many students also desire to preserve their cultural identity and value intelligibility in real-life contexts such as classrooms and job interviews. The study highlights the importance of acknowledging learners’ identities, goals, and the role of English as a global lingua franca. These insights suggest the need for more inclusive, identity-affirming pronunciation pedagogy that balances clarity with cultural respect in EFL settings, particularly within Islamic higher education.